Optimalisasi Ritme Sirkadian Melalui Aktivitas Fisik sebagai Strategi Anti-Penuaan: Tinjauan Pustaka - I Gusti Ayu, Nitya Indira; I Dewa Ayu, Inten Dwi Primayanti (PT Kalbe Farma Tbk., 2026)
Aging is a complex, multifactorial biological process characterized by progressive decline in physiological function and increased vulnerability to chronic diseases. This process is closely associated with circadian rhythm dysfunction, an endogenous 24-hour biological regulatory system that plays a crucial role in maintaining homeostasis through the regulation of metabolism, immune function, and the sleep-wake cycle. Circadian dysregulation not only accompanies aging but may also accelerate degenerative processes and increase the risk of various chronic diseases. Physical activity is recognized as a potent non-photic zeitgeber capable of modulating and strengthening bothcentral and peripheral circadian rhythms. The mechanisms involved include regulation of clock gene expression, modulation of core body temperature, alterations in hormonal, and effects on metabolic pathways and cellular energy sensors. This literature review discusses theinteraction between circadian rhythms, physical activity, and the aging process, and examines how optimization of circadian rhythm through appropriately planned physical activity may contribute as a progressive anti-aging strategy. Such an approach has the potential to supportimproved healthspan and preservation of physiological function with advancing age.